2017
DOI: 10.1016/j.sjpain.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Couples coping with chronic pain: How do intercouple interactions relate to pain coping?

Abstract: AbstractBackground and aimsPain is not merely an isolated experience occurring within the person. It takes place in a wider social context, including the immediate social relationships that the person is a part of. The aim of this paper is to provide an overview of how intercouple interactions might influence pain coping in couples coping with chronic pain. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 49 publications
(64 reference statements)
1
16
0
4
Order By: Relevance
“…Partners who often become the primary caregiver and source of emotional support for the patients while also dealing with their own emotions of witnessing their loved one suffer make significant adjustments and changes to their daily living and also long-term life plans. Pain becomes a shared stressor between the couple who confer shared meaning to the experience and employ mutual coping strategies [24]. This dyadic conceptualization of coping with pain recognizes the interdependence between intimate relationships and opens a new understanding of how coping with pain can affect their relationship and wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…Partners who often become the primary caregiver and source of emotional support for the patients while also dealing with their own emotions of witnessing their loved one suffer make significant adjustments and changes to their daily living and also long-term life plans. Pain becomes a shared stressor between the couple who confer shared meaning to the experience and employ mutual coping strategies [24]. This dyadic conceptualization of coping with pain recognizes the interdependence between intimate relationships and opens a new understanding of how coping with pain can affect their relationship and wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…social support, pain-related cognitions). Prenevost & Reme (2017) describe the consistent relationship between couples functioning and psychological distress in pain samples. McKillop and colleagues (2017) found that poor social support was predictive of depressive symptoms in patients with pain at one year.…”
Section: Psychological Distress and Copingmentioning
confidence: 96%
“…When the significant other showed comforting and caring behavior towards the chronic pain patient, the pain increased in contrast to a situation without the significant other [ 13 ]. Findings by Prenevost and Reme [ 15 ] also underline the importance of a significant other on pain coping strategies. During the process of dealing with pain, the interaction between the significant other and the pain patient is an important underlying factor.…”
Section: Learning Mechanismsmentioning
confidence: 99%